RELIGIOUS ACTIVITIES AS HIDDEN CURRICULUM IN MADRASAHS: THE CONSTRUCTION OF RELIGIOUS CULTURE IN CHARACTER FORMATION - Aulia Diana Devi; Sutiah; Moh. Padil; RAHMATULLAH ISMA'IL (STAI Ma'had Aly Al-Hikam Malang, 2025)
This study examines religious activities in madrasahs as a form of hidden curriculum that contributes to the construction of religious culture and the formation of students’ character. Using a qualitative approach with a library research design, this study analyzes various relevant literature on Islamic education, hidden curriculum, and character education. The findings indicate that religious activities such as congregational prayer, Qur’anic recitation, and other ritual practices are not merely formal obligations, but function as implicit pedagogical instruments that shape students’ values, attitudes, and behaviors. Through repetitive practices and social interactions within the madrasah environment, these activities construct a religious culture that fosters discipline, social responsibility, and spiritual awareness. Furthermore, the concept of hidden curriculum provides a theoretical framework to understand how values are transmitted indirectly through daily practices and institutional culture. However, the effectiveness of religious activities depends on their implementation. When carried out only as routine formalities without reflective understanding, their transformative impact becomes limited. Therefore, this study highlights the importance of integrating reflective and contextual approaches in managing religious activities, supported by teacher exemplification and a conducive institutional environment. This research contributes to the discourse on Islamic education by emphasizing the role of experiential learning and implicit value transmission in fostering holistic character development in madrasahs. Keywords: Hidden curriculum; Religious activities; Madrasah education; Religious culture. Abstrak Penelitian ini mengkaji kegiatan keagamaan di madrasah sebagai bentuk kurikulum tersembunyi yang berkontribusi pada pembangunan budaya keagamaan dan pembentukan karakter mahasiswa. Dengan menggunakan pendekatan kualitatif dengan desain penelitian perpustakaan, penelitian ini menganalisis berbagai literatur yang relevan tentang pendidikan Islam, kurikulum tersembunyi, dan pendidikan karakter. Temuan tersebut menunjukkan bahwa kegiatan keagamaan seperti shalat berjamaah, pembacaan Al-Qur'an, dan praktik ritual lainnya bukan sekadar kewajiban formal, tetapi berfungsi sebagai instrumen pedagogis implisit yang membentuk nilai, sikap, dan perilaku siswa. Melalui praktik berulang dan interaksi sosial dalam lingkungan madrasah, kegiatan ini membangun budaya keagamaan yang menumbuhkan disiplin, tanggung jawab sosial, dan kesadaran spiritual. Selanjutnya, konsep kurikulum tersembunyi memberikan kerangka teoritis untuk memahami bagaimana nilai-nilai ditransmisikan secara tidak langsung melalui praktik sehari-hari dan budaya kelembagaan. Namun, efektivitas kegiatan keagamaan tergantung pada pelaksanaannya. Ketika dilakukan hanya sebagai formalitas rutin tanpa pemahaman reflektif, dampak transformatifnya menjadi terbatas. Oleh karena itu, penelitian ini menyoroti pentingnya mengintegrasikan pendekatan reflektif dan kontekstual dalam mengelola kegiatan keagamaan, didukung oleh teladan guru dan lingkungan kelembagaan yang kondusif. Penelitian ini berkontribusi pada wacana pendidikan Islam dengan menekankan peran pembelajaran pengalaman dan transmisi nilai implisit dalam mendorong pengembangan karakter holistik di madrasah. Kata kunci: Kurikulum tersembunyi; Kegiatan keagamaan; pendidikan madrasah; Budaya religius.